ข้อจำกัดของสหประชาชาติในการให้ความคุ้มครองสิทธิมนุษยชน - กมลรัตน์ อินอุตมา (จุฬาลงกรณ์มหาวิทยาลัย, 2000)
The objective of this thesis is to study the constraints of the United Nations in protecting human rights. Human rights are prescribed as fundamental in the United Nations Charter from 1945. One of its important aim is to achieve international co-operation in promoting and encouraging respect for human rights and for fundamental freedoms for all without distinction as to race, sex, language, or religion. Many bodies have been established to fulfil this aspiration. The General Assembly and the Economic and Social Council (ECOSOC) which are the principal organs and the Commission on Human Rights, a subsidiary organ of the ECOSOC all are delegated main responsibility to engage in all human rights issue. Many others have been established to assist the United Nations for the protection of human rights, but up to present, the violations of human rights remain continually in every region. This research tries to find out what are the main factors that make the UN protection of human rights ineffective. The study proves that although by the international law the United Nations has legitimacy to intervene in the violation of human rights committed by the sovereigh states, in practice it faces with big constraints in various member states. The main problems are the lack of cooperation of member states with the UN human rights bodies and the lack of authoritative power of the UN against member states violating the international laws on human rights.